Answer:
13
Step-by-step explanation:
Given the equation h(x) = 2x²
To solve for h(-2) + 5 then, we need to break the problem into two parts
First, we will solve for the function h(x) at x = -2
h(x) = 2x² so
h(-2) = 2(-2)²
h(-2) = 8
Knowing this, we can plug 8 into our original expression for h(-2)
8 + 5
This gives us 13
Heyyyyyy new friends and I have no clue what the answer is cause I don’t feel like reading that but anyway yea nfs?
Answer:
m∠SRT = 33° ∵ m∠QRT = m∠SRT
Step-by-step explanation:
Given the diagram,
RT bisects ∠SRQ, and m∠QRT = 33°
RT bisecting ∠SRQ means RT will bisect ∠SRQ into two equal angles, which are:
m∠QRT = m∠SRT
as
m∠QRT = 33°
so
m∠SRT = 33° ∵ m∠QRT = m∠SRT
Answer:
<8
Step-by-step explanation:
They are the same angle degree.